The Inclusion of Cultural Content in Civilization Course Classes: A Procedure to Motivate Students or Frustrate Them? - Mohamed Cherif Seddiki (The Journal of Studies in Language, Culture and Society)
The use of cultural content in EFL classes has recently driven a rising interest among language instructors. Yet, there are conflicting attitudes about the appropriate teaching strategies and classroom activities designed for classes as such. 67% of EFL instructors see these classes are mere attempts to develop linguistic competency while the rest, university lecturers particularly, see that a laser focus should be on cultural knowledge. They do believe that the mastery of language is secondary compared to critical thinking and textual analyzing making EFL classes more than a language hub for developing reading, writing and speaking. This eventually calls the content of culture-based lessons together with the relevant teaching techniques to inquiries. The course of civilization has incited talks about what relevant topics and teaching practices can help achieve the objectives of this course. The concern of this paper is to bridge the gap between the teachers’ attitudes on what final objectives this course should target: developing the learners’ linguistic ability, enriching their cultural knowledge or both. It aspires to refine the content of the course and share some of the best teaching practices. Surveying some education scholars’ recommendations together with the latest teaching practices suitable for this kind of classes might help speculate what might wholly turn civilization class around. A survey is additionally conducted to find out what might make civilization course very appealing. This attempt is significant in the sense it pinpoints the importance of cultural content in teaching English as an international language, and its pivotal role in diversifying teaching materials and motivating learners if handled appropriately.